Relationship of DNA aneuploidy with distinctive features of oral potentially malignant disorders: A cytological analysis of 748 cases - Yanyi Tang; Lijun Liu; Chenxi Li; Wei Liu; Linjun Shi (Elsevier, 2022)
Our previous study reported that clinical features, including the lateral/ventral tongue and non-homogeneous lesions, were associated with increased risk of malignant changes in cytological samples from oral potentially malignant disorders (OPMDs). This cross-sectional study aimed to evaluate the frequency and risk of DNA aneuploidy in the series of 748 patients with OPMD. The cut-off value of aneuploidy was defined as DNA index ≥3.5. We found that the frequency of DNA aneuploidy was higher in OPMD patients >60 years old, and in those with lateral/ventral tongue sites, non-homogeneous lesions, and high-grade dysplasia, than in control group (P < 0.01). Consistently, the risk of aneuploidy occurrence was higher in patients >60 years old (1.69-fold; P = 0.022), in those with lateral/ventral tongue sites (2.35-fold; P < 0.001), and in those with high-grade dysplasia (3.19-fold; P < 0.001). Collectively, increased frequency and risk of DNA aneuploidy occurred in OPMD patients aged over 60 years with high-grade dysplasia located at the lateral/ventral tongue. These patients should be required to intensive management and follow-up.